Towards zero-energy architecture : new solar design. - Guzowski, Mary, ....- (London : Laurence King, 2010)
Towards Zero-energy Architecture is a much needed call for the design professions to redefine architecture to help alleviate ecological problems. This book explores the theories, practices, and principles of new approaches to solar architecture that foster both design excellence and low-energy use.